The Differences of First Stage Labor with Lemon and Lavender Aromateraphy in Panongan Health Centre Tangerang Regency - Azzahroh, Putri; Maman, Arita Yuanita; Rukmaini (International Journal of Midwifery and Health Sciences, 2023)
Background: Severe pain during labor can cause fatigue in the mother so that there is a risk of prolonged labor which can endanger the mother and fetus. Panongan Community Health Center, Tangerang Regency, Banten in January-March 2022 there were 142 deliveries, 11 mothers (7.8%) of whom delivered SC at the mother's request because they could not stand the pain of labor. Purpose: To determine the differences in labor pain in the first stage of labor for mothers who were given lavender aromatherapy and lemon aromatherapy at the Panongan Health Center, Tangerang Regency, in 2022. Methods: Quasy experimental design study with two group pre-post test design. The sample in this study was 30 respondents using a purposive sampling technique. Data were analyzed using paired sample t-test and Independent T-Test which were previously tested for normality and homogeneity. Results: Pain in the first stage of labor in women giving birth before giving lavender aromatherapy averaged 6.00 and after being given lavender aromatherapy an average of 3.20 with an average difference of 2.80. Pain in the first stage of labor in women giving birth before giving lemon aromatherapy averaged 6.47 and after being given lemon aromatherapy averaged 1.73 with an average difference of 4.74. The results of bivariate analysis with paired sample t-test giving lavender aromatherapy a value of 0.000 and lemon aromatherapy a p value of 0.000. Independent T-Test results posttest p value 0.002. Conclusion: there are differences between lavender aromatherapy and lemon aromatherapy on first stage labor pain among mothers. It is hoped that giving lemon and lavender aromatherapy can be applied thoroughly in Indonesian health services.